Research on AC–DC High-Frequency Interaction Mechanism and Valve-Side High-Frequency Oscillation Suppression Strategy of Flexible HVDC Converter - Liwu Tan; Yang Zhang; Yanan Wu; Yu An; Yuhan Huang (International Transactions on Electrical Energy Systems)
High-frequency oscillation phenomena in flexible high-voltage direct current (HVDC) transmission systems significantly compromise operational reliability in major power infrastructure projects. This study addresses the critical gap in device-level high-frequency interaction mechanisms by developing a comprehensive AC–DC high-frequency model for flexible DC converter valves using convolution Fourier series analysis. The research establishes quantitative relationships between DC voltage oscillations and system parameters, identifying that high-frequency harmonics in converter valve pole voltage are primarily influenced by high-frequency control components, module voltage ratings, line parameters, and valve currents. A novel hardware solution integrating a DC matching reactor designed for impedance matching with AC reactance is proposed, avoiding modifications to existing system parameters. This approach is complemented by a dual-strategy control scheme combining switching frequency optimization and active damping techniques. Experimental validation using a 7-module physical test system demonstrated that the hardware solution reduced high-frequency harmonics by approximately 50% when impedance matching conditions were satisfied. Real-time simulations of a ±420 kV HVDC system further confirmed the effectiveness of the combined approach, reducing total harmonic distortion from 5.74% to 0.80% while decreasing power module switching frequency from 1500 Hz to 120 Hz. The high-frequency modeling framework and suppression strategies presented in this study provide substantial improvements in both theoretical understanding and practical mitigation techniques for high-frequency oscillations in flexible HVDC systems, offering enhanced stability for modern power transmission infrastructure.